LEARNING OF STUDENTS IN THE DIGITAL AGE ACCORDING TO YONISOMANASIKARA PRINCIPLES OF SCHOOLS UNDER, PHRA NAKHON SI AYUTTHAYA EDUCATIONAL SERVICE AREA 1 - Srivichai, Suddhipong; Thitapanyo, PhrakhrusamuThong; Thitavaddhano, PhramahaYannawat; Wilairadtanakun , Aroonrad; Boonpoo, Manassanan (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) study the learning process of students in the digital age, 2) develop the learning process of students in the digital age based on the principle of Yonisomanasikra, and 3) evaluate the learning of students in the digital age based on the principle of Yonisomanasikra in schools under Phra Nakhon Si Ayutthaya Educational Service Area 1. This research was a mixed-methods study consisting of quantitative research using a questionnaire of 50 administrators, teachers, and students of Maharat “Prachanimit” School. Data were analyzed using basic statistics, namely frequency, percentage, mean, and standard deviation. Qualitative research was conducted by interviewing 15 administrators, teachers, and experts in the learning process of students in the digital age. Focus group discussions were conducted with 10 qualified persons. Data were analyzed using content analysis. The results of the research found that: 1) Learning process of students in the digital age (1) The school designed content together with administrators, teachers, and student representatives by planning the teaching and learning process based on the learning and teaching principles to the solve problems planning or increasing the efficiency of students and three things must be considered were process, media, and students. (2) Designing learning activities by co-organizing activities with teachers and students, specifying clear activities, and clearly defining the roles of the groups and each member, and defining a clear work structure. (3) Designing the communication process together with teachers and students, determining the media and learning resources by integrating the Yonisomanasikra thinking method, but still lacking in the clarity of the activities. 2) Developing the learning process of students in the digital age according to the Yonisomanasikra principles of schools under the Phra Nakhon Si Ayutthaya Educational Service Area 1, consisting of designing content, designing learning activities, and designing the communication process of activities by integrating the Yonisomanasikra principle, aiming for learners to see the value of developing the mind for learning and living with the Yonisomanasikra thinking method, which was the thinking of true value, false value, and the thinking of good, bad, and solutions or developing the mind according to the religion they believe in, able to solve various problems more easily, adjust misunderstandings, and reducing the chances of conflicts among students, creating more interactions between teachers and students, students had more self-confidence, more creativity and innovation, and align with the core curriculum of the ministry of education according to the learning plan, practicing to be a good Buddhist, the subject of developing wisdom (Yonisomanasikra), and 3) The results of the assessment of students' learning in the digital age according to the Yonisomanasikra principles of schools under the Phra Nakhon Si Ayutthaya Educational Service Area 1 using the learning plan, practice of being a good Buddhist, regarding the development of wisdom (Yonisomanasikra), the overall of 3 aspects was found to be at a high level. All aspects were at a high level, namely, the aspect of designing learning activities, the aspect of designing communication processes, and the aspect of designing contents, respectively.